Changes in transmucosal buprenorphine utilization for opioid use disorder treatment during the COVID‐19 pandemic in Kentucky. Issue 1 (24th May 2022) - Lei, Feitong; Lofwall, Michelle R.; Freeman, Patricia R.; Slade, Emily; Vickers‐Smith, Rachel; Slavova, Svetla
Abstract: Purpose: With surging opioid‐involved overdoses, maintaining access to opioid use disorder (OUD) treatment is critical during the COVID‐19 pandemic. We examined changes in transmucosal buprenorphine prescribing for OUD treatment in Kentucky after the national COVID‐19 emergency declaration, with a focus on rural‐urban differences. Methods: Using 2019‐2020 prescription monitoring data, we performed segmented regression analysis for an interrupted time series design to evaluate changes in weekly rates (per 100, 000 residents) of dispensed prescriptions, unique individuals with dispensed prescriptions, and average days' supply for dispensed prescriptions of transmucosal buprenorphine. Findings: The weekly rates of dispensed prescriptions and unique individuals with dispensed prescriptions were higher for rural residents than urban residents. After the national COVID‐19 emergency declaration, rural and urban residents experienced similar immediate drops in the rate of dispensed prescriptions (rural –33.4; urban –24.3) and unique patients with dispensed prescriptions (rural –25.0; urban –17.1), followed by similar sustained increases. Both measures surpassed the prepandemic levels in mid‐June 2020. Patients residing in urban areas received averagely longer prescriptions at baseline (urban: 11.0 days; rural: 10.5 days). The average weekly days' supply increased in the week after the national emergency declaration, but the estimated increase was higher ( P = .004) for urban (0.8 days) versus rural (0.5 days) residents. Conclusions: Transmucosal buprenorphine utilization increased during the COVID‐19 pandemic after experiencing interruption during the initial weeks of the pandemic. Future studies should evaluate the contribution of the relaxed telemedicine buprenorphine prescribing regulations during the COVID‐19 national emergency on initiation and maintenance of buprenorphine treatment.